Kajian Cider sebagai Alternatif Penganekaragaman Produk Kopi - Suharyono Apno Sugito (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2012)
Coffee is an important export commodity from Indonesia. There are not many processed product from coffee, and sincecoffee is a delightful refreshing beverage, it is interesting to make product diversivication from coffee. An alternative processing could be a cider. Coffee used in this research were decaffeinated, Robusta and Arabica coffee. The amount of added sugar were 15 %, 20 %, and 25 %. Natural cultures, combination of Sacharomyces cerevisiae and Acetobacter xylinum, combination of Sacharomyces ludwigii and Acetobacter xylinum, combination of S. cerevisiae, S. ludwigii, and A. xylinum were used as starters. The parameters observed included: reducing sugar content, alcohol, total tertitrasi acid, pH and Organoleptic Test (color, aroma, taste, clarity, and general acceptance). Coffee cider with the highest overall acceptance score was made from decaffeinated coffee, with 20 % sugar addition and combination of S. ludwigii and A. xylinum as starter.The result of correlation analysis showed a negative significant correlation between reducing sugar content and aroma of coffee cider. Positive significant correlation were found between total titrable acidity and aroma, taste and overall acceptance of coffee cider.ABSTRAKKopi merupakan komoditas ekspor penting Indonesia. Tidak banyak produk olahan dari kopi, yang lebih dikenalsebagai minuman menyegarkan dan menyenangkan, sehingga menarik untuk membuat diversifikasi produk kopi. Salah satu alternatif adalah pengolahan cider. Kopi yang digunakan dalam penelitian ini adalah kopi tanpa kafein, Robusta dan Arabika. Jumlah gula yang ditambahkan adalah 15 %, 20 %, dan 25 %. Kultur alami, kombinasi Sacharomyces cerevisea dan Acetobacter xylinum, kombinasi Sacharomyces Ludwigii dan Acetobacter xylinum, kombinasi S. cerevisiae, S.Ludwigii , dan A.xylinum digunakan sebagai starter. Parameter yang diamati meliputi: kadar gula pereduksi, alkohol, total asam tertitrasi, pH dan Uji Organoleptik (warna, aroma,rasa, kejernihan, dan penerimaan umum). Cider kopi dengan skor penerimaan keseluruhan tertinggi dibuat dari kopi tanpa kafein, dengan penambahan gula 20 % dan kombinasi S. Ludwigii dan A. xylinum sebagai starter. Hasil analisis korelasi menunjukkan hubungan signifikan negatif antara pengurangan kadar gula dan aroma sari kopi. Hubungan yang bermakna positif ditemukan antara keasaman total dan aroma, rasa dan penerimaan keseluruhan cider kopi.